2011
DOI: 10.1002/pssa.201127595
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of surface proton transfer doping in pentacene based organic thin‐film transistors

Abstract: A number of studies show that chemical modification of the semiconductor-dielectric interface can be used to control the threshold voltage (V th ) of organic thin film transistors (OTFTs). A promising chemical functionality to achieve that are acidic groups, which -at the semiconductor-dielectric interfacehave been used to realize chemically responsive OTFTs and easy to fabricate inverter structures. Especially for pentacene based OTFTs, the underlying chemical and physical mechanisms behind the acid-induced V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…For further details see ref. [88] (b) Adapted with permission. [88] Copyright 2011, Wiley-VCH Verlag GmbH & Co. KGaA.…”
Section: Densely Packed Dipole Layersmentioning
confidence: 99%
“…For further details see ref. [88] (b) Adapted with permission. [88] Copyright 2011, Wiley-VCH Verlag GmbH & Co. KGaA.…”
Section: Densely Packed Dipole Layersmentioning
confidence: 99%
“…Using a drift‐diffusion based approach we do this avoiding effects like diffusing metal atoms, morphological inhomogeneities caused by different film growth on the electrodes and the dielectric, trap‐states at the interfaces, and the field or carrier‐density dependence of the mobility. Many of these effects can be readily integrated in our device model and we found the latter two essential for getting fully quantitative agreement with experimental data (including hysteresis effects), but not for explaining the then investigated general trends 5, 30. Thus, we here focus on the most fundamental processes at the contacts which allows us to extract and, importantly, also to explain the intrinsic properties of the charge‐injecting contacts.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Second, ion diffusion is well-known to play an important role in material stability (or lack thereof) in inorganic thin-film solar-cell materials. [18,19] Herein, we take af irst step toward understanding ionic migration in OIHP materials,b ys tudying the migration of interstitial hydrogen from first principles.O ur interest in hydrogen motion is stimulated by the well-known protonconducting phenomena in oxide perovskites, [20,21] which could also be relevant for OIHPs.I ndeed, hydrogen is ap ertinent defect species in both prototypical organic [22,23] and inorganic semiconductors, [24,25] in part because it is ubiquitous in many processes of organic and inorganic chemistry.S pecifically, water is asolvent for lead-based OIHPs.Recent experiments have demonstrated the beneficial effect of mild moisture exposure on film growth, [26] and it was suggested that (partial) decomposition of OIHPs as ar esult of water may trigger ap roton-migration process. [27] Furthermore,t he organic cation could be deprotonated, thus indicating ap ossible intrinsic source of migrating hydrogen.…”
mentioning
confidence: 99%